Education and leadership: Indispensable for Nigeria's economic development - OBASANJO, Olusegun (Institutional Knowledge at Singapore Management University, 2016)
The former President of Nigeria (1999 to 2007), Olusegun Obasanjo, talks about the nation’s evolving transformation in this interview with Philip Zerrillo.